Evaluation of Sustainability of Brazilian Ethanol Production: A model in System Dynamics - Arnoldo Jose de Hoyos Guevara; Orlando Roque da Silva; Haroldo Lhou Hasegawa; Délvio Venanzi (BBR: Brazilian Business Review)
System dynamics is an approach to analyze the behavior of complex systems, such as the productive chains, strictly considering the inherent characteristics. This approach is based on mathematical concepts of nonlinear processes developed in mathematics and physics and consolidated in engineering. The concepts inherent in this approach assists in creating a mathematical model that represents a production chain by using computer simulation. Thus, the main objective of this paper is to present the formalization of the dynamic model of assessing the sustainability of Brazilian ethanol production. We analyzed the external environment and the scenarios needed for a deeper understanding of relation of cause and effect, causal loops and diagrams of flows and stocks because of the awareness stage, with regard to understanding the problems involved, according to methodology known as design science.